2002
DOI: 10.1016/s0020-7292(01)00579-3
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian male sexual activity during pregnancy

Abstract: Personal beliefs significantly affect sexual relationships between Nigerian husbands and their pregnant wives, making approximately one-third of husbands engage in extra-marital relationships as a way to satisfy their unmet sexual need during pregnancy. There is a need to educate husbands and their pregnant wives on sexual matters during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 4 publications
6
28
2
2
Order By: Relevance
“…[35] Another study stated that personal beliefs may affect sexuality and reduce the frequency of sexual intercourse during pregnancy when compared to pre-pregnancy period. [36] According to our data, it can be speculated that partners with low educational level and women who experienced preconceptional sexual disorders have a higher risk of suffering from sexual dysfunction during pregnancy. Therefore, counseling these population about sexuality may help to improve sexual functions by correcting the misbeliefs on this issue.…”
Section: Discussionmentioning
confidence: 71%
“…[35] Another study stated that personal beliefs may affect sexuality and reduce the frequency of sexual intercourse during pregnancy when compared to pre-pregnancy period. [36] According to our data, it can be speculated that partners with low educational level and women who experienced preconceptional sexual disorders have a higher risk of suffering from sexual dysfunction during pregnancy. Therefore, counseling these population about sexuality may help to improve sexual functions by correcting the misbeliefs on this issue.…”
Section: Discussionmentioning
confidence: 71%
“…A considerable number of pregnant women were reported to abstain coitus during pregnancy. 3,5,9,11 In a study by Onah et al, 14 the frequency of coitus was reported to be decreased from 3.2 per week before pregnancy to 1.8 per week during pregnancy. Our results are in agreement with these previous reports showing that the coital activity diminished once the pregnancy was confirmed.…”
Section: Discussionmentioning
confidence: 95%
“…A number of reports exist in the literature to correlate with our findings. 3,[6][7][8][9]11,14 Sexual interest was reported to be unchanged or slightly decreased in the first trimester, variable in the second trimester and decreased sharply at the end of the third trimester. 3,5,6,9 Lubrication is intensified during pregnancy, whereas orgasm is variable.…”
Section: Discussionmentioning
confidence: 99%
“…Según los relatos de los participantes del estudio, ellos no formarían parte de las estadísticas de varones que buscan sexo con otras mujeres durante el embarazo de su pareja (Brtnicka et al, 2009;Onaha et al, 2002). Lo que quedó bien establecido es que las creencias y concepciones de los varones se vinculan con las prácticas sexuales que realizan con sus cónyuges en el embarazo, determinando su frecuencia, forma, exclusividad e intensidad.…”
Section: Discussionunclassified